Professional ASP.NET MVC 3.0 - Galloway, Jon., Haack, Phil., Wilson, Brad (Wiley-Blackwell, 2011)
This in-depth book shows you step-by-step how to use MVC 3.0. You'll learn both the theory behind MVC 3.0, as well as walk through practical tutorials, where you'll create a real-world application.